A Microring Resonator Based Negative Permeability Metamaterial Sensor - Yao-Zhong Lan; Ting-Hua Li; Jun Sun; Ming Huang; Jing-Jing Yang (Sensors, 2011)
Metamaterials are artificial multifunctional materials that acquire their material properties from their structure, rather than inheriting them directly from the materials they are composed of, and they may provide novel tools to significantly enhance the sensitivity and resolution of sensors. In this paper, we derive the dispersion relation of a cylindrical dielectric waveguide loaded on a negative permeability metamaterial (NPM) layer, and compute the resonant frequencies and electric field distribution of the corresponding Whispering-Gallery-Modes (WGMs). The theoretical resonant frequency and electric field distribution results are in good agreement with the full wave simulation results. We show that the NPM sensor based on a microring resonator possesses higher sensitivity than the traditional microring sensor since with the evanescent wave amplification and the increase of NPM layer thickness, the sensitivity will be greatly increased. This may open a door for designing sensors with specified sensitivity.